OCA Oracle Database 11g. : SQL fundamentals 1: a real-world certification guide : ace the 1Z0-051 SQL fundamentals 1 exam, and become a successful DBA by learning how SQL concepts work in the real world /: SQL fundamentals 1: a real-world certification guide : ace the 1Z0-051 SQL fundamentals 1 exam, and become a successful DBA by learning how SQL concepts work in the real world. (2011) - Ries, Steve
No abstract available